Analisis Kemampuan Komunikasi Matematika Siswa pada Materi Jarak dan Waktu - Hidayati, Nurul; Amaliyah, Aam; Inayah, Siti Wardatul; Maulida, Zahra (ARZUSIN, 2022)
This study aims to describe students' mathematical communication skills on the subject of distance and time in class IV.a SDN Belendung Tangerang. The subjects of this study were students of class IV.a totaling 29 people. The results of the research show that student communication with the teacher at the time of learning the material is quite active and can follow the material. This research is a type of qualitative descriptive research and uses cooperative learning methods. The results showed that on the criteria students could state the problems of the questions. This research departs from the background of learning carried out by teachers in general is by lecturing concepts, principles, and laws in a ready-made form to students. Learning in this way proved to be less successful because it was found that students' understanding was not yet comprehensive on the material being taught, so that students were less proficient in formulating their understanding to be able to solve or solve problems that still revolved around the material given previously. This research uses direct observation into class IV.a and learning outcomes tests. Hopefully, after conducting this research and interview, we and the team will get the answers we are currently researching and make the learning much better than before this research was held.